A comprehensive analysis of the 21st century's research trends in English Mobile Learning: a bibliographic review of the literature. Issue 1 (6th December 2021) - Khodabandelou, Rouhollah; Fathi, Masood; Amerian, Mohammad; Fakhraie, Mohammad Reza
Abstract : Purpose: This study examines the importance of English Mobile Learning research as a foundation for lifelong and sustainable education from different points of view, including those of technology innovation experts, psychologists and educators. It aims to explore the current status and relevant research trends through the application of bibliometric mapping and bibliometric analysis. Design/methodology/approach: For this study, all Web of Science records (in total 5, 343) from 2000 to 2020 in the field of English Mobile Learning were analyzed using the VOSviewer and CiteSpace software tools. The WoS built-in functions, including "Refine" and "Analyze, " were employed to perform the bibliometric analysis. The study further analyzed a sample of the five most-cited articles to identify the previous studies with the highest quality or impact. Findings: The results showed that research in English Mobile Learning is growing quickly and steadily with a noticeable emphasis on various device-based technologies and applications. The study also discusses the key implications for research institutions, education policymakers and academicians, and identifies the most prominent avenues for future research on English Mobile Learning. Moreover, the results shared in this review highlight the most important and emerging areas of research in the field. Originality/value: This article is the most recent bibliographic review of literature that particularly addresses the English Mobile Learning research during the past two decades.